Gaining momentum...!: strategy solidarity spirituality of justice-based peace - Jerry (Dindigul Vaigarai Publishing House, 2008)
Contributed papers on the life and achivements of Xuanzang, ca. 596-664, Buddhist priest presented at an international seminar; includes papers on Buddhist cultural heritage.